MACRO- AND MICROECONOMIC GUIDELINES FOR INCREASING THE ECONOMIC EFFICIENCY OF ENTERPRISES IN THE SERVICE SECTOR - MAIBORODA, Vladyslav (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article defines the conceptual characteristics of the economic efficiency of the entrepreneurial sector. According to the analysis of scientific works, it is proposed to divide the benchmarks for increasing the economic efficiency of enterprises in the service sector according to macro- and microeconomic characteristics. The significant influence of the state on increasing the economic efficiency of enterprises in the service sector is emphasized, and its interests include GDP growth and the expansion of the capacity of the domestic service market, an increase in the number of effectively functioning enterprises in the service sector and their investment and innovative technological activity, and an increase in the share of implementation of knowledge-intensive high-tech services in the sphere of services, increase of tax payments, insurance contributions and other mandatory payments by enterprises in the service sector, formation of a highly developed market infrastructure in the service sector, prevention of shadowing and monopolization of the business environment and development of fair competition in the service sector, improvement of the material situation and quality of life of the population, creation and increasing the number of new competitive jobs and diversifying the forms of employment of the population, etc. At the microeconomic level, the benchmarks for increasing the economic efficiency of enterprises in the service sector include increasing revenues and profits, improving financial stability, strengthening solvency and liquidity, increasing the profitability of service implementation, increasing business activity and improving competitive positions, improving the efficiency and intensity of the use of material and technical means, growth of investment activity and capitalization of business processes, etc.